THE CHANGES OF NITRIC OXIDE SERUM LEVELS IN PATIENTS WITH END-STAGE RENAL DISEASE (World Bulletin of Public Health, 2022)
Chronic Renal Failure (CRF) is a term used to describe an irreversible decline in renal function that often occurs over a number of years. In many situations, an initial insult to the kidney function leads to additional nephron loss and the requirement for dialysis or kidney transplantation End stage renal disease (ESRD) is the term used to describe this ailment. Patients with chronic kidney disease (CKD) are at an increased risk of cardiovascular (CVD) morbidity and mortality, mainly due to atherosclerosis. Decreased production or reduced bioavailability of nitric oxide (NO) can result in endothelial dysfunction (ED). Multiple mechanisms are known to cause a state of NO deficiency in patients with CKD. this study compares the levels of (NO), and its ratios, in ESRD patients and healthy controls